Divine Providence : the Bible, Virgil, Orosius, Augustine, and Dante. - Schildgen, Brenda Deen (Bloomsbury Publishing, 2012)
Holding divine intervention responsible for political and military success and failure has a long history in western thought. This book explores the idea of providential history as an organizing principle for understanding the divine purpose for humans in texts that may be literary, historical, philosophical, and theological. Providential History shows that, with Virgil and the Bible as authoritative precursors to late antique views on history, the two most important political thinkers of the late antique Christian world, Orosius and Augustine, produced the theories of Christian politics and.